Balancing Innovation and Ethics: The Controversy of Artificial Intelligence in Higher Education Policy Management - Rizkiyah; Izzatul Munawwaroh; Chanda Chansa Thelma (EDUCARE: Jurnal Ilmu Pendidikan, 2024)
Technological innovations, particularly artificial intelligence (AI), present new challenges and opportunities in higher education policy management. This study examines how higher education institutions can balance implementing innovative AI technology with ethical considerations. Using a qualitative approach with a case study method, the research involved university leaders, lecturers, and students as subjects. Data collection was conducted through in-depth interviews, observations, and policy document analysis, while data analysis included data reduction, presentation, and conclusion drawing. The findings reveal that implementing AI in policy management requires addressing ethical aspects, such as data privacy, algorithmic bias, and transparency. Institutions can educate stakeholders about the benefits and risks of AI through communication and training initiatives while adopting ethical strategies, such as clear AI usage policies and stakeholder involvement in decision-making. Leveraging effective digital platforms, institutions can foster an environment that supports innovation while adhering to ethical principles. This research significantly contributes to the development of higher education management policies by emphasizing the importance of balancing innovation and ethics in the digital era.